Romantic relationships in emerging adulthood: An intercultural approach - Louki, Eleni (Homo Virtualis, 2025)
This study examines romantic relationships during the period of emerging adulthood, with a particular focus on Southern European countries, specifically Greece, Italy, and Spain. Adopting a qualitative, phenomenological and interpretative approach, it seeks to explore the lived experiences of romantic relationships within the broader sociocultural environment that shapes them. The research addresses a significant gap in the existing literature concerning romantic relationships in Southern Europe, particularly the impact of prolonged co-residence with family on relational development and autonomy. The study is grounded in Arnett’s theory of emerging adulthood, as well as the developmental frameworks proposed by Shulman & Connolly and Hochberg & Konner. Data were produced through multimodal interviews with 11 participants aged 18 to 24. The interview design integrated narrative, visual, and appreciative inquiry techniques. Thematic Analysis was employed using the QualCoder QDA software, through which five central themes were identified. The findings indicate that early cultural narratives contribute to the formation of idealized expectations regarding romantic relationships, which gradually evolve into more realistic conceptions over time. Participants demonstrated an ambivalent orientation toward love, intimacy, and commitment, reflecting a tension between the longing for deep emotional connection and the desire to maintain personal freedom. Within this context, technology plays a dual role, facilitating communication and connection while also enabling controlling and intrusive behaviors. Finally, family involvement was found to delay the process of individuation and restrict the exploration of sexuality. Within this context, technology serves a dual role, facilitating communication and connection while enabling controlling and intrusive behaviors. Finally, family involvement was found to delay the process of individuation and restrict the exploration of sexuality. Overall, this study adopts an intercultural approach, emphasizing the dynamic interplay between cultural norms, family structures, and individual experiences in shaping the meaning and expression of romantic relationships among emerging adults in Southern Europe.